Faktor Yang Berhubungan Dengan Anemia Pada Ibu Hamil Trimester III Di Puskesmas Simpang Kiri Kota Subulussalam Provinsi Aceh Tahun 2018 - Pemiliana, Putri Diah; Oktafirnanda, Yuka; Santi, Irwa (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Anemia generally occurs throughout the world, especially in developing countries and in low socio-economic groups. Overall, anemia occurs in 45% of women in developing countries and 13% in developed countries. The purpose of this study was to determine the factors associated with anemia in third trimester pregnant women. The design of this study was an analytical survey with a cross sectional approach. The population of this study amounted to 55 people and the sample in this study were all third trimester pregnant women. The data used is secondary data. Univariate and bivariate data analysis techniques with Chi-square test. The results of the study showed that 55 respondents were 27 anemic and 24 were not anemic, based on the chi square test of adherence to anemia with anemia, p = 0.021 <0.05, the relationship between parity and anemia in trimester III pregnant women was obtained p = 0.006 <0.05, the relationship between education and anemia in third trimester pregnant women obtained p = 0.032 <0.05. The conclusions in this study were the relationship of adherence to Fe tablet consumption, education, parity with anemia in third trimester pregnant women. It is recommended to the Simpang Kiri Health Center to provide counseling on how to consume the right Fe tablets and make posters of danger of anemia in pregnant women and efforts to prevent anemia in pregnant women.